The Influence of Work Discipline and Public Service Systems on Community Satisfaction in One-Stop Services in Sawahlunto City - Safputri, Yollanda Eka; Nirwana, Ida; Yeni, Afni (ProBisnis : Jurnal Manajemen, 2023)
This research was conducted at the One Stop Service Office in Sawahlunto City. The purpose of this research was to determine the effect of work discipline and the public service system on the satisfaction of service users. The method used in this study is a quantitative method using SPSS 22. In this study, the population of people who carry out public services at the One-Stop Service in Sawahlunto City is 34 people. By using accidental sampling, a sample of 34 people was obtained. The data collection technique used is by using a questionnaire or questionnaire. Based on multiple linear regression analysis of work discipline and public service system variables on community satisfaction, Y = 1.257 + 0.745 X1 + 0.0377 X2 + e. From the t-test conducted, it was found that work discipline variable X1 had a significant effect on community satisfaction with a variable value of 3.407 > 2.039 and a significance level value of 0.002 <0.05. Variable X2 public service system has an influence on community satisfaction with a variable value (2.119 > 2.039) and a significance level value of 0.002 <0.05. Judging from the f test conducted, it was found that work discipline and public service systems have a simultaneous effect on community satisfaction, that fcount > ftable (15,034 > 3.29), with a significance probability of 0.000 <0.05. This can be seen from the R Square value of 0.492 or 49.2% and the rest is influenced by other variables not included in this study of 50.8%.